Pengaruh Hasil Investasi, Underwriting, Dan Dana Tabarru’ Terhadap Laba Perusahaan Asuransi Jiwa Syariah Di Indonesia Periode 2017-2021 - Azis Kembara; Fithrah Kamaliyah (Jurnal Literasi Akuntansi, 2023)
Purpose: This study aims to provide evidence regarding the effect of investment returns, underwriting and tabarru funds on sharia life insurance companies. Method: The research method and type of data used are quantitative data. This study used a sample of sharia unit life insurance companies registered with the Financial Services Authority during the 2017-2021 period. Determination of the sample by using purposive sampling in order to obtain as many as 11 sample companies with a total sample of 55 observational data. Data analysis in this study used panel data analysis with the help of the Eviews 12 software computer program. The methods used were descriptive statistics, panel data tests, and classical assumption tests. Then testing the hypothesis using the coefficient of determination test, t-test and F-test. Finding: The results of this study show that partially investment returns have an effect on Islamic insurance profits, underwriting has no effect on Islamic insurance profits, tabarru' funds have an effect on Islamic insurance profits and simultaneously the results investment, underwriting and tabarru' funds affect the profit of sharia insurance.